Prediction of the effects of size and morphology on the structure of water around hematite nanoparticles - Spagnoli, Dino; Gilbert, B.; Waychunas, G.; Banfield, J. (Pergamon-Elsevier Science Ltd, 2009)
Compared with macroscopic surfaces, the structure of water around nanoparticles is difficult to probe directly. We used molecular dynamics simulations to investigate the effects of particle size and morphology on the time-averaged structure and the dynamics of water molecules around two sizes of hematite (a-Fe2O3) nanoparticles. Interrogation of the simulations via atomic density maps, radial distribution functions and bound water residence times provide insight into the relationships between particle size and morphology and the behavior of interfacial water. Both 1.6 and 2.7 nm particles are predicted to cause the formation of ordered water regions close to the nanoparticle surface, but the extent of localization and ordering, the connectivity between regions of bound water, and the rates of molecular exchange between inner and outer regions are all affected by particle size and morphology. These findings are anticipated to be relevant to understanding the rates of interfacial processes involving water exchange and the transport of aqueous ions to surface sites.